El desarrollo agro-industrial del cultivo de la yuca en la Costa Atlantica de Colombia. Cuarto informe sobre el desarrollo de la agroindustria de yuca seca durante el periodo julio 1984-junio 1985 - Best, R.; Ospina, B. (Centro Internacional de Agricultura Tropical (CIAT), Proyecto Cooperativo DRI-CIAT, 1985)
From July 1984 to June 1985, 13 new drying plants were established on the Atlantic Coast of Colombia for a total of 20 plants. During the 1984-85 campaign, these plants processed 7158 t fresh cassava (total of 3006 t dry cassava), representing an increase of 217 percent over the previous campaign. Of the 20 plants, only 14 gave profits. Plants giving losses were late in initiating operations due to delays in the construction; these are expected to operate normally during the next campaign. The profitability of some of the new plants was also affected by the fact that the groups established to operate them were conformed by farmers of low or no capacity to produce cassava. Therefore, the enterprises were subjected to the supply of cassava by non-members, representing no guarantee of attraction for membership to the cooperative or association. The attraction price of fresh cassava continues to be the main factor in determining the economic profitability of the drying process. During the 1st semester of 1985, a program was established to produce improved cassava seed, at both the farmer and national research center levels. Thetechnical advisory teams in each department have favorably increased their no. and coverage of cassava plants; new markets for dry cassava have also been established. Trade union actions among farmers involved in the project have increased. Likewise, significant advances were achieved in the creation of an officially recognized federation of dry cassava producers of the Atlantic Coast, FEPROYUSCA. Future plans include the establishment of 6 new cassava drying plants in Cordoba, 6 in Sucre, 7 in Bolivar, 1 in Atlantico, and 1 in Cesar. It is estimated that dry cassava production in the 35 plants that will operate on the Atlantic Coast during the 1985-86 campaign will reach a total of approx. 5500 t. (AS-CIAT)